Extension Agents’ Perception on the Use of ICTs for Agricultural Extension Services in Kwara State, Nigeria - Ifabiyi Oluwaseun; Raufu Sanusi; Ololade Abdulrahman; Faith EVWIERHURHOMA (Al-Qadisiyah Journal For Agriculture Sciences)
The application of modern communication technologies and digital devices to agricultural extension service deliveries could enhance the productivity of the extension agents through provision of accurate, timely and relevant information to the farmers. This study examined the Extension agents’ Perception on the use of ICTs for agricultural extension services in Kwara State, Nigeria. About 105 extension agents were randomly selected for the study. Statistical tools such as frequency count, percentage and mean score were used to analyse the data. The result showed that about 98.1 % of the respondents were willing to use ICTs devices for agricultural extension services. The usage of mobile phone for calls (mean =2.88) was the most frequently used ICTs. Digital/ICTs makes extension agents to easily linkup with researchers in order to solve the farmers’ problems (mean =4.47) was highest ranked perception statement. High cost of the Digital/ICTs devices (mean=2.62) was the most severe factor limiting the use of ICTs for extension services. The study therefore recommends that the Extension agents should be empowered to be able to have access and use the various ICTs for agricultural extension activities as they were willing to use it.